The Influence of al-Sahihayn on Popular Hadith Literatures: The Case of Khazinah al-AsrarJalilah al-Adhkar - Abdullah, WH; Zarif, MMM; Borham, A; Hashim, A (Univ Sultan Azlan Shah, 2024)
The compilations of authentic hadith by al-Bukhari (d.870) and Muslim (d.875) known collectively as al-Sahihayn serve for the Sunnis as the second highest source of religion after the Quran. The stringent methods in hadith selection and appraisal in these books have contributed to their credibility and reliability as a primary religious source, and many succeeding works attempted to emulate them, though with varying results. Some popular hadith literatures have also utilized al-Sahihayn as their main source of hadith quotation to enhance their status of acceptance, notwithstanding some compromises and modifications. This is particularly the case with a 19th century hadith compilation known as Khazinah al-Asrar Jalilah al-Adhkar by Muhammad Haqqi al-Nazilli (d.1884). Thus, this paper aims to delve into this topic in further details. It attempts to analyze the role and influence of al-Sahihayn on Khazinah al-Asrar, the extent of compliance of its author with the former, and the overall implication of its extensive methodology on succeeding hadith works, particularly in Southeast Asia.